Philippines : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper discusses reasons behind rise of inflation in Philippines. The paper focuses on inflation developments and the monetary policy framework in the Philippines. It employs a global latent factor model to decompose inflation into common drivers and idiosyncratic factors for a sample of 62 countries. Based on these results, it then models inflation in different regions and presents the single country, single equation model and conducts out of sample forecasts to determine consistency with the medium-term inflation target. The common factors modeling of inflation suggests that inflation in the Philippines depends on world commodity price developments and movements in the US dollar effective exchange rate. However, theory suggests that domestic cyclical conditions also matter. We assess the importance of these variables by estimating a Phillips curve augmented by world commodity prices and the nominal exchange rate for 2000-2013. Using the Akaike-Schwartz criterion, the optimal lag length is found to be four. Given the potential for serial correlation and heteroskedasticity, we use the Newey-West standard errors to find the consistent estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet